Effects of the tobacco–maize relay intercropping pattern on soil nutrients and soil microbial diversity - Yang, Kang; Zi, Shuhui; Ouyang, Chengren (Frontiers in Microbiology, 2025)
The imbalanced soil nutrient status caused by the long-term monoculture of flue-cured tobacco are a concern. The tobacco–maize relay intercropping, widely used in Yunnan, may improve soil nutrients by enhancing the soil microbial community, but this remains unexplored. This study employed high-throughput sequencing technology to examine soil microbial diversity under tobacco monoculture and tobacco–maize relay intercropping, using the varieties Hongda and K326, respectively. The results indicated that tobacco–maize relay intercropping significantly enhanced root biomass compared to tobacco monoculture, with no significant effect on aboveground biomass. This intercropping treatment also significantly improved soil physicochemical properties, including soil pH, total phosphorus, available phosphorus, and available potassium, which was associated with an increase in the soil microbial community (as indicated by the Chao1 and Shannon indices). Specifically, the abundance of arbuscular mycorrhizal fungi, Nitrospira, and Acidobacteria increased, but the abundance of Chloroflexi decreased. Therefore, these findings suggest that tobacco-maize relay intercropping can improve soil physicochemical properties and enhance soil nutrient supply.